NAAC Accreditation… A Commitment to Quality - Dr. L. N. Seshagiri (INTERNATIONAL JOURNAL OF RESEARCH IN COMMERCE, IT, ENGINEERING AND SOCIAL SCIENCES ISSN: 2349-7793 Impact Factor: 6.876, 2011)
Quality is an essential prerequisite for any system or organization to survive and higher education is no exception. Continued effort to improve any institution of higher learning through introspection, innovation and improvisation can alone bring in quality and accountability. Any attempt at introspection, leads to self-evaluation. Comparative review of such an analysis and renewed attempts to achieve excellence. Quality is not a goal, but a moving target, for which benchmarking is necessary and a sincere attempt to achieve such landmarks on the way to quality alone can result in excellence.